2010
DOI: 10.1016/j.physbeh.2010.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Eating behaviors of children in the context of their family environment

Abstract: Both a family history of obesity and early childhood obesity have been identified as strong predictors of adult obesity risk. The finding that parental obesity, maternal obesity in particular, increases a child’s risk for developing obesity suggests that either shared genes, or environment, or likely a combination of both may promote overeating and excessive weight gain in children. Parents not only create food environments for children’s early experiences with food and eating, but they also influence their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
109
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(121 citation statements)
references
References 111 publications
(94 reference statements)
5
109
0
7
Order By: Relevance
“…The family's food environment plays a major role in a child's food consumption (Bassett, Chapman, & Beagan, 2008;Birch & Davison, 2001;Kral & Rauh, 2010). Parents determine which foods and how much food children can access, and they serve as models for their children's food choices through their own food attitudes, preferences and behaviours (Birch, Savage, & Ventura, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The family's food environment plays a major role in a child's food consumption (Bassett, Chapman, & Beagan, 2008;Birch & Davison, 2001;Kral & Rauh, 2010). Parents determine which foods and how much food children can access, and they serve as models for their children's food choices through their own food attitudes, preferences and behaviours (Birch, Savage, & Ventura, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that supplementation of n-3 PUFA at discrete developmental stages such as during pregnancy or at weaning reduces the number of TEB in rats (Hilakivi-Clarke et al 2002bOlivo and Hilakivi-Clarke 2005) and subsequent tumour burden. Lifelong exposure to a consistent n-3 PUFA level, however, is more reflective of human dietary patterns, as dietary intakes of children tend to be similar to those of their parents (Kral and Rauh 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Por outro lado, importa destacar o papel da aprendizagem na aquisição de preferências alimentares em jovens (crianças e adolescentes), quer a aprendizagem formal (sobre alimentos saudáveis versus não saudáveis, por exemplo) quer a aprendizagem informal 2,3 . Nos processos de aprendizagem informal os pais desempenham um papel fundamental, nomeadamente através da modelação quanto a hábitos alimentares (aprendizagem vicariante, para os jovens) e da disponibilidade alimentar permitida (para além, obviamente, das recomendaç ões/permissões diretas quanto às escolhas alimentares dos jovens) 4 .…”
Section: Introductionunclassified
“…Sabe-se também que as práti-cas parentais potenciam a opção por determinados alimentos através da exposição repetida a esses alimentos 4,7 .…”
Section: Introductionunclassified